Learning and the Lifespan: What’s Sex Got to Do With It? - Kohtz, Amy Stave; Frye, Cheryl A. (Frontiers in Neuroscience, 2020)
Engagement in sexual behavior can impact neurosteroidogenesis, in particular production of the prohormone testosterone (T) and likely its subsequent metabolism to 5α-androstane-3α-17β-Diol (3-Diol) or aromatization to estradiol (E2). Androgens and their metabolites vary across the lifespan and impact many behaviors, including cognition, anxiety, and sexual behavior. Thus, we hypothesized that mating may alter cognitive performance via androstane neurosteroids in an age- and experience- dependent manner. We first investigated if exposure to mating during memory consolidation could enhance performance in the novel object recognition task (NOR). Male rats were trained in NOR and then immediately exposed to mating-relevant or control stimuli. Following a four hour inter-trial interval (ITI), male rats were tested for object memory. Male rats that were exposed to a receptive female during the ITI had better performance in NOR. We then investigated if these effects were due to novelty associated with mating. Male rats were exposed to mating-relevant stimuli and identified as sexually-responsive (SR) or non-responsive (SNR) based on a median split of engagement in mating with the stimulus female. We found that a brief history (10 min session daily for 5 consecutive days) of sexual history substantially influenced performance in the NOR task, such that SR males had better performance in the NOR task, but only when presented with the opportunity to mate during the ITI. As T levels substantially decrease with age in male rodents, we investigated whether the effects of long-term sexual experience (10 months) influenced neurosteroids and NOR performance in mid-aged (12 months old) males. Mid-aged SR males maintain neural T; however, they have decreased neural E2 and decreased cognitive performance at 12 months compared to mid-aged SNR rats. In sexually experienced rats, those with better cognitive performance had greater levels of T metabolites, (e.g. 3-Diol in mated SR males, E2 in mid-aged SNR rats). While naïve males that were mated during the ITI had better cognitive performance, T metabolites were decreased compared to controls. These findings suggest that T metabolites, but not the prohormone, may influence learning dependent on sexual proclivity, experience, and proximate opportunity to mate.